The Aesthetics of Free Speech - Roberts, J. author. aut Link
VIII, 277 p.
Keywords: The Aesthetics of Free Speech: Rethinking the Public Sphere is one of the first books to theoretically explore the relationship between free speech and the public sphere. By drawing upon Marxist theory the author, John Michael Roberts, demonstrates how liberal theorists frequently construct an abstract aesthetic of 'rational', 'cultivated' and 'competent' discussion which then serves as a norm through which certain utterances can be humiliated and excluded from participating fully within the public sphere. However, the author also shows how excluded utterances develop their own aesthetic of free speech and how this aesthetic then comes back to haunt the bourgeois public sphere.